Project for the Architecture of Transition - Leslie Buerk; Daniel Herr; Karl Puljak (Oz, 1990)
Death as a subject of architecture is the art of the depiction of the invisible. It transgresses the field of architectural signification delineated by utility and purpose and imposes an unavoidable need to examine and question expressive limits of architecture.